2012
DOI: 10.1002/chem.201200752
|View full text |Cite
|
Sign up to set email alerts
|

Pd/Light‐Accelerated Atom‐Transfer Carbonylation of Alkyl Iodides: Applications in Multicomponent Coupling Processes Leading to Functionalized Carboxylic Acid Derivatives

Abstract: The atom-transfer carbonylation reaction of various alkyl iodides thereby leading to carboxylic acid esters was effectively accelerated by the addition of transition-metal catalysts under photoirradiation conditions. By using a combined Pd/hν reaction system, vicinal C-functionalization of alkenes was attained in which α-substituted iodoalkanes, alkenes, carbon monoxide, and alcohols were coupled to give functionalized esters. When alkenyl alcohols were used as acceptor alkenes, three-component coupling reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 110 publications
1
35
0
5
Order By: Relevance
“…22 When irradiated with light, this radical/radical/reduction process begins with the abstraction of an iodine atom from 30 to form radical 33 . This primary radical then adds to olefin 31 to form 34 , which can add to an equivalent of CO to form keto-radical 35 .…”
Section: Transition Metal-mediated Domino Reactionsmentioning
confidence: 99%
“…22 When irradiated with light, this radical/radical/reduction process begins with the abstraction of an iodine atom from 30 to form radical 33 . This primary radical then adds to olefin 31 to form 34 , which can add to an equivalent of CO to form keto-radical 35 .…”
Section: Transition Metal-mediated Domino Reactionsmentioning
confidence: 99%
“…The discovery that transition metals such as Pd 0 in the presence of light could significantly accelerate this transformation has stimulated much effort recently to extend the scope of application of ATC [65]. Extensive mechanistic studies showed that photoexcited Pd 0 species may promote the formation of the Ccentered radical through SET with the formation of a Pd I I species, which is later trapped by the acyl radical to produce an acyl palladium complex, reacting in the last step with the nucleophile [66]. This mechanism was preferred to the putative migratory insertion of CO into an alkyl-palladium bond formed through oxidative addition of Pd 0 onto R-I.…”
Section: Metal-mediated Atom-transfer Radical Carbonylationmentioning
confidence: 99%
“…1 Recent studies have developed carbonylations 2 and carboxylations 3 of alkyl electrophiles, which have been much less studied than aryl or vinyl substrates. These catalytic transformations are proposed to involve radical intermediates produced from the activation of alkyl halide substrates.…”
mentioning
confidence: 99%